Hubungan Status Gizi dengan Perkembangan Motorik Kasar Pada Balita Umur 1-5 Tahun di Desa Pucangombo Kecamatan Tegalombo Kabupaten Pacitan. - Sumini, Sumini (Jurnal Delima Harapan, 2016)
Based on the data SKDN September 2015 in the village of Pucangombo district of Tegalombo,district of Pacitan , there were 132 children, the number of children who weighed consists of 3children (2.5%) with poor nutritional status, 10 children (8.3%) with malnutrition status and 107children (89.16%) with good nutritional status. Based on data from the nutritional status of infants,infants with malnutrition status progress has not in accordance with their age. Nutritional status ofchildren influence the development of gross motor development at the children, so it can determinefurther developments. Based on preliminary study on 26 September 2015 in the village ofPucangombo Tegalombo Pacitan from 10 children found 8 respondents had good nutritional status,with of appropriate gross motor development, 2 respondents less nutritional status, with gross motordevelopment of the doubts. This study aims to determine the relationship of nutritional status andgross motor development in under five year children.Quantitative research with cross sectional study design. This study conducted in the Village ofPucangombo Tegalombo Pacitan in September 2016. The population was children aged 1-5 yearsamounted to 90 children and 72 children as with samples taken by accidental sampling techniques.The independent variable was nutrient status and the dependent variable was gross motordevelopment. Instruments with observation sheet, microtoa, scales, and KPSP. Data analysed bySpearman Rank at the 0.05 level of significance.The results of this study indicated that the nutritional status of children the majority of 62respondents (86.1%) has good nutritional status. Gross motor development in children aged 1-5 yearsalmost entirely 63 respondents (87.5%) with appro priate development. There was a relationship ofnutritional status with gross motor development in children aged 1-5 years in the village of the tPucangombo Tegalombo, Pacitan district, with a significance level of p <0.005 it was 0.000 with acoefficient correlation of 0.925, which means the level of closeness was very strong.Based on the results of the study are expected to mothers add insight and knowledge onnutrition of children under five nutritional needs are met in an optimal and gross motor developmentof infants according to age.